Research Progress of the Liquid-Phase Exfoliation and Stable Dispersion Mechanism and Method of Graphene - Li, Liangchuan; Zhou, Ming; Jin, Long; Liu, Lincong; Mo, Youtang; Li, Xiao; Mo, Zhaoyou; Liu, Zhenzhao; You, Shengli; Zhu, Hongwei (Frontiers in Materials, 2019)
Graphene is a honeycomb hexagonal 2D crystal nanomaterial with a thickness of only 0.334 nm. It has been widely used and studied because of its ultra-thin 2D nano-characteristics and excellent electrical, thermal, optical and mechanical properties. With the continuous in-depth study of graphene, the liquid phase dispersion of graphene has also achieved breakthroughs. This review summarises the research progress of the liquid phase exfoliation mechanism, exfoliation method, stable dispersion mechanism and dispersion method of graphene in recent years. The research situations of Hamaker constant theory in exfoliation mechanism and Hansen solubility coefficient theory in stable dispersion mechanism are mainly discussed. The shortcomings of the research are summarised, and analyses the graphene liquid phase dispersed in the important challenge in the future. The stable dispersion method of graphene is also summarised. In the future, the π-π interaction is the most potential method for studying graphene stabilization.